Systemic Venous Recanalization: Iliocaval and Superior Vena Cava Reconstruction in Children - Bertino, Frederic J. (Seminars in Interventional Radiology, 2025)
Restoring venous patency and flow is crucial for pediatric patients with superior vena cava (SVC), IVC, and iliac vein occlusion, and advancements in venous recanalization and stent reconstruction have proven safe and efficacious in the adult population, with techniques from adult patients adapted to manage these conditions in younger individuals. Endovascular therapy has advanced significantly, improving device and stent technologies, imaging modalities, and procedural techniques. This study reviews indications, technical considerations, and outcomes for venous stenting in pediatric patients, focusing on SVC syndrome, IVC atresia, and iliac vein compression. This guide is a reference for interventional radiologists to optimize outcomes through precise stent selection and procedure execution.
Keywords: pediatric; interventional radiology; venous recanalization; venous occlusion; sharp recanalization; stent; angioplasty